2000
DOI: 10.1007/s100210000028
|View full text |Cite
|
Sign up to set email alerts
|

Altering Rainfall Timing and Quantity in a Mesic Grassland Ecosystem: Design and Performance of Rainfall Manipulation Shelters

Abstract: Global climate change is predicted to alter growing season rainfall patterns, potentially reducing total amounts of growing season precipitation and redistributing rainfall into fewer but larger individual events. Such changes may affect numerous soil, plant, and ecosystem properties in grasslands and ultimately impact their productivity and biological diversity. Rainout shelters are useful tools for experimental manipulations of rainfall patterns, and permanent fixed-location shelters were established in 1997… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
226
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(244 citation statements)
references
References 33 publications
13
226
2
3
Order By: Relevance
“…Each RaMP comprises a fixed-location, 14 x 9 m rainout shelter over intact, native grassland (Fay et al 2000(Fay et al , 2003. Each shelter consists of a clear (UV transparent) polyethylene roof to exclude natural rainfall, two 4 m 3 reservoirs to collect and store up to 10 cm of rainfall, and an overhead irrigation system to reapply (at 2.5 cm hr -1 ) the stored rainfall.…”
Section: Rainfall Manipulation Plots (Ramps)mentioning
confidence: 99%
See 2 more Smart Citations
“…Each RaMP comprises a fixed-location, 14 x 9 m rainout shelter over intact, native grassland (Fay et al 2000(Fay et al , 2003. Each shelter consists of a clear (UV transparent) polyethylene roof to exclude natural rainfall, two 4 m 3 reservoirs to collect and store up to 10 cm of rainfall, and an overhead irrigation system to reapply (at 2.5 cm hr -1 ) the stored rainfall.…”
Section: Rainfall Manipulation Plots (Ramps)mentioning
confidence: 99%
“…Each shelter consists of a clear (UV transparent) polyethylene roof to exclude natural rainfall, two 4 m 3 reservoirs to collect and store up to 10 cm of rainfall, and an overhead irrigation system to reapply (at 2.5 cm hr -1 ) the stored rainfall. Thus, the shelter design allows for complete and efficient experimental control of the quantity, timing and variability in rainfall inputs (Fay et al 2000). Rainfall is applied to each RaMP using 13 sprinkler heads to ensure …”
Section: Rainfall Manipulation Plots (Ramps)mentioning
confidence: 99%
See 1 more Smart Citation
“…but rainfall manipulation experiments demonstrate that plant responses to rainfall can also depend significantly on the timing of rainfall distribution (17,18). Recent theoretical work also highlights the complexity of plant dependence on water.…”
mentioning
confidence: 99%
“…2). Some studies have shown that the seasonal distribution of rainfall affects ecosystem productivity, biological diversity, and soil nutrients cycling (Fay et al, 2000;Weltzin et al, 2003;Peng et al, 2012), as well as the biological activity of microbes and plants. Thus, nitrification and denitrification processes driven by microbial activity and N availability must be affected.…”
mentioning
confidence: 99%